COMMUNITY ENGAGEMENT IN NATIONAL DEFENCE: THE COMPREHENSIVE DEFENSE CONCEPT (HANRUH) - Zainol, Noor Azmi Mohd; Taib, Khairul Nizam; Ismail, Ariffin; Zainol Abidin, Zahimi; Sofian, Mohd Haniff; Abd Hamid, Fazli; Bala, Bilcher; Salleh, Mohd Shaiful Mohd (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This article explores the involvement of the East Malaysian public in national defence through the Comprehensive Defence or Pertahanan Menyeluruh (HANRUH) concept, based on interviews with community in Sabah and Sarawak. The HANRUH concept emphasizes that national defence is a shared responsibility, extending beyond the military to include civilians, public sector workers, and community members. This study investigates key themes such as the public’s understanding of HANRUH, the ways individuals can contribute to national defence, challenges in implementing the concept, and the role of technology and innovation in strengthening national security. The findings reveal that while the concept of HANRUH is not widely understood, there is recognition among respondents that individuals, especially those in community and educational roles, can contribute by promoting safety awareness and participating in emergency preparedness. However, challenges like limited resources, inadequate training opportunities, and a lack of awareness are significant barriers. The study also highlights the role of social media and mass communication in raising awareness, with respondents agreeing that these platforms can help engage the public in defence activities. Additionally, the involvement of youth in national defence is seen as crucial, with many respondents advocating for early education and training to build long-term security awareness. In conclusion, this study calls for greater public education, accessible training, and the strategic use of technology to encourage widespread participation in national defence, ensuring a more resilient and united Malaysia.